Pengaruh Motivasi Belajar, Fasilitas Belajar dan Disiplin Belajar terhadap Prestasi Belajar Siswa MTss Al Azhar Tanjungbumi Bangkalan - Zainal Abidin; Nelud Darajaatul Aliyah; Didit Darmawan (Journal on Education, 2024)
In order to realize good learning achievement, teachers as educators are expected to have good learning motivation within themselves as well as the supporting capacity of learning facilities for the teacher, as well as improving student learning discipline well. This research has a very important and relevant aim, especially in the context of improving the quality of education at MTsS AL AZHAR Paseseh, Tanjungbumi District, Bangkalan Regency. This research uses a quantitative approach that will be used in this research to measure the influence of variables such as learning motivation, learning facilities, and learning discipline on student learning achievement. Based on this research, it can be concluded that there is a significant correlation between learning motivation, learning facilities, and learning discipline and student learning achievement at MTsS AL AZHAR Tanjungbumi Bangkalan.